DUR ARI KAPIJI (HARI TERPILIH YANG PENUH KEMURKAAN) - Edi Suisno (SURYA SENI, 2009)
Dur Ari Kapiji (The Elected Angrily Day. Play of “Dur Ari Kapiji”(DAK) forms a play that has as a starting point of an investigation history of Jayakatwang’s rebellion which is related with a conﬂ ict of “Monsserat”  created by Emanuel Robles. This investigation compares heroism between  Jayakatwang’sand Simon Bolivar’s. Eventually, both of the characters inspire the play of DAK apparently with theme and conﬂ ict which are the same more or less but with new invention characters.In addition to be inspirited that matters, the play of DAK is also formed in tragedy. The tragedy forms a play about human sufferings in order to realize their desires or to face their reality fate. While the play of DAK is a tragedy which experiences the top of esthetic achievement in the past, but the tragedy inthe play of DAK is also appeared in critical spirit to face nowadays problems.Afterwards the play of DAK will be formed into a realism staging through representation approach. The realization of the elected representation approach is guided by conﬂ ict combination from ‘authentic’ DAK manuscript which is the source of directing creativity. Besides that, addition and modiﬁ cation of themanuscript occur as an effort in ‘sharpening’ the play dynamics. Hence, the forms in ‘radically’ adapting and processing of the manuscript are not become a part of modiﬁ cation concept at all. The approach or representation form occurs through represents a visual form as the ‘selected’ realism which is guided by outwardly of ‘impression’ and not only displace the reality on the stage.Keywords: Jayakatwang, Monsserat, and Representation